2022
DOI: 10.1007/s00203-022-03309-7
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis thrives in dual-species biofilm models under iron-rich conditions

Abstract: Escherichia coli (E. coli) and Enterococcus faecalis (E. faecalis) are pathogenic strains that often coexist as an intestinal ora in humans and are prone to cause bio lm-associated infections such as gastrointestinal tract and urinary tract infections. Earlier studies have demonstrated that E. faecalis bio lm can metabolize ferrous ions in iron-rich environments and promote bio lm growth under in-vivo conditions. However, the in uence of iron transporters on dual-species bio lm growth and the nature of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This could be explained in that Gp49 does not have RNase activity and its RNA binding ability may stabilize, thus upregulate the genes in the hem operon. A recent study showed that the Gram-positive bacterium Enterococcus faecalis ( E. faecalis ) was stained safranin color instead of violet during Gram staining in the iron-supplemented condition (300 μM) [ 20 ]. The 11-fold increase of iron storage in bacterial cells reported in the study is consistent with our observation in the Gp49 overexpressing B. subtilis .…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained in that Gp49 does not have RNase activity and its RNA binding ability may stabilize, thus upregulate the genes in the hem operon. A recent study showed that the Gram-positive bacterium Enterococcus faecalis ( E. faecalis ) was stained safranin color instead of violet during Gram staining in the iron-supplemented condition (300 μM) [ 20 ]. The 11-fold increase of iron storage in bacterial cells reported in the study is consistent with our observation in the Gp49 overexpressing B. subtilis .…”
Section: Resultsmentioning
confidence: 99%
“…In E . faecalis , FeoB has been reported to promote biofilm formation and antibiotic resistance by potentially binding and importing Fe2+ into the cytosol [ 38 ]. On the other hand, the presence and biological role of ferrous iron transport protein in S .…”
Section: Discussionmentioning
confidence: 99%
“…Ferrous iron transport protein is a membrane protein that is essential for Fe (II) uptake in bacteria [37]. In E. faecalis, FeoB has been reported to promote biofilm formation and antibiotic resistance by potentially binding and importing Fe2+ into the cytosol [38]. On the other hand, the presence and biological role of ferrous iron transport protein in S. lugdunensis has not yet been clearly determined, other than a previous study that found that the deletion of accessory gene regulator (agr) involved in quorum sensing upregulated ferrous iron transport protein B [39], indicating a potential involvement in biofilm formation.…”
Section: Plos Onementioning
confidence: 99%
“…UTIs are caused by Gram-positive bacteria (e.g., E. faecalis, S. aureus , group B Streptococcus (GBS)), Gram-negative bacteria (e.g., E. coli, K. Pneumonia, Proteus mirabilis ( P. Mirabilis ) , P. aeruginosa ), as well as some fungal species (e.g., Candida spp.) ( Flores-Mireles et al, 2015 ; Govindarajan et al, 2022 ; Jacobsen and Shirtliff, 2011 ). UTI starts when uropathogens from the gut or bacteria from the skin around the urethral opening migrate to the urethra and then progress to the bladder.…”
Section: Antimicrobial Coating On Urinary Cathetersmentioning
confidence: 99%